Analysis of the implementation of Government Regulation No. 46 2013 in the calculation of PT ABC’s income tax payable 2013/2014 - Naniek Noviari (Universitas Hayam Wuruk Perbanas, 2014)
This research is a case study of the implementation of the Government Regulation No. 46 in the calculation of income tax payable 2013/2014 of PT ABC (a villa management company in Bali). This study uses quantitative and qualitative data, i.e. PT ABC’s Profit/Loss reports in 2012/2013, PT ABC’s Ledger of 2013, and the Notary Deed of the Establishment of PT ABC, which are collected using documentation technique. The Data are analyzed through several stages; firstly, to determine whether or not PT ABC should implement Regulation No. 46 in the calculation of its income tax payable 2013/2014, secondly, to calculate and analyze the comparison of PT ABC’s income tax payable 2013/2014 between using the Regulation No 46 scheme and regular scheme. It is found that PT ABC’s total income tax payable 2013, which is calculated using the Regulation No. 46 scheme, is lower than that of using the regular scheme, while the opposite condition occurs in 2014. This will potentially lead to a conflict of interest in the management of PT ABC that could potentially lead to act of tax evasion. This research uses the assumptionthat PT ABC’s Profit/Loss in 2014 has the same condition as PT ABC’sProfit/Loss in 2013. The future researchers can perform similar study in other companiesby using the actual report of Profit/Loss in 2014 and/or compare it with the condition ofProfit/Loss of the company for the next 3 consecutive years.